KONTRIBUSI GREEN SUKUK DALAM PEMBIAYAAN BERKELANJUTAN - Setiawan Bin Lahuri; Muhammad Maulana Rizki (Department of Sharia Economics, Faculty of Islamic Economics and Business, Universitas Islam Ibrahimy Banyuwangi, Indonesia, 2025)
Infrastructure development plays a crucial role in supporting public welfare and economic growth. The main challenge in Indonesia is how to maintain a balance between infrastructure development and environmental preservation. Green Sukuk has emerged as a sustainable, Sharia-based financing instrument that offers an alternative for the government to fund environmentally friendly projects. This study aims to analyze the role of Green Sukuk in sustainable development in Indonesia and assess its compliance with Fatwa DSN-MUI No. 137 of 2020 on Sukuk. The research method employs a literature review using secondary data from scholarly literature, papers, and regulations. The findings indicate that Green Sukuk makes a significant contribution to financing green projects such as renewable energy, energy efficiency, and waste management, supporting the achievement of the Sustainable Development Goals (SDGs). Fatwa DSN-MUI No. 137 of 2020 serves as an important guideline to ensure the alignment of Sukuk instruments with Sharia principles while enhancing investor confidence. Nevertheless, the implementation of Green Sukuk still faces challenges, including low levels of Sharia financial literacy, limited availability of green projects that meet the criteria, and regulatory constraints. A comprehensive strategy is needed to optimize the role of this instrument going forward.